Chronotype and Its Association With Body Mass Index and Binge Eating Behaviour among Undergraduate Students - Shamsudin, Juliana; Khoo , Le Xuan (International Journal of Allied Health Sciences, 2026)
Background: An individual's sleep-wake patterns are much influenced by their inclination for morning or evening activities, known as chronotype. According to recent studies, chronotype could affect eating behaviours and body mass index (BMI) among other facets of health. This aim of this study is to investigate the association among undergraduate students between the chronotypes and their correlation with body mass index (BMI) and binge eating behaviour. Methods: This cross-sectional study included 166 undergraduate students from USM Health Campus, with 86.1% females and a mean age of 21.1 ± 1.4 years. The Morningness-Eveningness Questionnaire (MEQ) and the 7-Item Binge-Eating Disorder Screener (BEDS-7) were used to assess chronotype and binge eating behaviour respectively. Meanwhile, BMI was calculated by measuring weight and height. Results: The chronotype distribution among university students indicated that 16.3% were categorised as morning types, 68.1% as intermediate types, and 15.7% as evening types. The mean chronotype score was 20.26 ± 8.37, signifying a moderate general preference with considerable individual variability. Binge eating behaviours are prevalent in 22.3% of university students, with a mean score of 3.04 ± 3.00. The incidence of overweight and obese students rose from 21.7% to 31.3% when assessed based on the new CPG Obesity guidelines. Conclusion: There were no associations between binge eating behaviour (p=0.431) and BMI (p=0.422) with the chronotypes discovered. More research is needed to shed light on the relationships between chronotype, BMI, and binge eating behaviour, as well as to identify other factors that may play a more important role in influencing BMI among university students.